PENERAPAN METODE SIMPLE ADDITIVE WEIGHTING DALAM SEBAGAI MODEL PEREKRUTAN KARYAWAN DI PT. MANDALA MULTIFINANCE - Rissa Ariyani; Riki Renaldo; Yansahrita Yansahrita (YHMM PUBLISHING, 2023)
The recruitment process is an initial process to select and ensure prospective employees who are to be recruited or selected to occupy positions that have been determined by the industry. In this research the authors used the Simple Additive Weighting (SAW) method or often known as the weighted sum method. This test will use data from seven prospective employee applicants. By using this method it will produce a Decision Support System that can assist in solving problems with the recruitment process for prospective employees. The Simple Additive Weighting method also selects the best alternative as well as several existing alternatives because there is a ranking process after determining the weight of each criterion. This decision support system can share problem solving with the Marketing Area Executive Coordinator for prospective employees and can share appropriate suggestions to improve the quality of decisions.